Intellectual Associations as Factor of Forming of European Cultural and Educational Space (XVI – XVII Centuries) - Оlena Нapchenko (Pedagogical Discourse, 2015)
The place and role of intellectual associations in creation of single European cultural and educational space, in the development of forms of educational activity that form personality have been studied in the article. It is underlined that due to the efforts of following by Ukrainian intelligentsia of XVI – XVII centuries humanistic traditions, the translation of values of European spiritual life onto the Ukrainian soil took place, the European standards of school and university education became firmly established, experience of attitude was formed toward the subject of educational process as to unique personality, carrier of high moral qualities.